The impact of General Psychological Training on the self-efficacy of Mothers whose Children Undergoing Surgery in Taleghani Pediatrics Hospital in Gorgan, Iran - Hossein Motahari Niya; Hamid Hojjati (Golestan University of Medical Sciences, 2019)
Background and objectives: Surgery in children around the world, including our country, is a stressful activity for mothers of children and reduces their self-efficacy in childcare. It is important to use psychological training approaches, especially in mothers, to improve their self-efficacy. The aim of this study was to investigate the effect of cognitive strategy training on reducing the stresses caused by Children's Surgery in mothers and on their self-efficacy. Methods: In an experimental study in Taleghani Pediatric Center in 1396, 60 mothers whose children had surgery were randomly selected and allocated to intervention and control groups. The general psychological training and stress management program was implemented for the intervention group. Data collection tool was a questionnaire of two-part parenting self-efficacy questionnaire (PSAM DEMO). Results: The independent t-test was not significantly different between the two groups before intervention (P-value = 0.72). However, after intervention, the level of self-efficacy in the intervention and control group showed a significant difference (P <0.01). Therefore, the level of self-efficacy in the control group was lower. ANOVA showed a significant difference between the intervention and control groups before and after the intervention (P <0.01). Eta of 0.47 shows that approximately 50% of the changes in the increase in self-efficacy of the mothers of children with preoperative surgery related to the intervention. Therefore, the mothers of the intervention group had more self-efficacy than the control group before surgery. Conclusion: Strategies for providing appropriate education for mothers with children undergoing surgery can be suggested as an effective approach to increasing the self-efficacy of mothers in all hospitals throughout the country.